TBLT implementation and evaluation: A meta-analysis. (September 2019) - Bryfonski, Lara; McKay, Todd H.
Task-based language teaching (TBLT) is an empirically investigated pedagogy that has garnered attention from language programs across the globe. TBLT provides an alternative to traditional grammar translation or present-practice-produce pedagogies by emphasizing interaction during authentic tasks. Despite several previous meta-analyses investigating the effect of individual tasks or short-term task-based treatments on second language (L2) development, no studies to date have synthesized the effects of long-term implementation of TBLT in authentic language classrooms. The present study uses meta-analytic techniques to investigate the effectiveness of TBLT programs on L2 learning. Findings based on a sample of 52 studies revealed an overall positive and strong effect ( d = 0.93) for TBLT implementation on a variety of learning outcomes. The study further examined a range of programmatic and methodological features that moderated these main-effects (program region, institution type, needs analysis, and cycles of implementation). Additionally, synthesizing across both quantitative and qualitative data, results also showed positive stakeholder perceptions towards TBLT programs. The study concludes with implications for the domain of TBLT implementation, language program evaluation, and future research in this domain.